Coagulation and Fibrinolytic Profile of Paediatric Patients Undergoing Cardiopulmonary Bypass - Chan, Anthony K C; Leaker, Michael; Burrows, Frederick A; Williams, William G; Gruenwald, Colleen E; Whyte, Linda; Adams, Margaret; Brooker, Lu Ann; Adams, Helen; Mitchell, Lesley; Andrew, Maureen (Thrombosis and Haemostasis, 1997)
The haemostatic system and the use of heparin during cardiopulmonary bypass (CPB) have been studied extensively in adults but not in children. Results from adult trials cannot be extrapolated to children because of age-dependent physiologic differences in haemostasis. We studied 22 consecutive paediatric patients who underwent CPB at The Hospital for Sick Children, Toronto. Fibrinogen, factors II, V, VII, VIII, IX, XI, XII, prekallikrein, protein C, protein S, antithrombin (AT), heparin cofactor II, α2-macroglobulin, plasminogen, α2-antiplas- min, tissue plasminogen activator (tPA), plasminogen activator inhibitor, thrombin-AT complexes (TAT), D-dimer, heparin (by both anti-factor Xa assay and protamine titration) and activated clotting time (ACT) were assayed perioperatively. The timing of the sampling was: pre heparin, post heparin, after initiation of CPB, during hypothermia, post hypothermia, post protamine reversal and 24 h post CPB. Plasma concentrations of all haemostatic proteins decreased by an average of 56% immediately following the initiation of CPB due to haemodilution. During CPB, the majority of procoagulants, inhibitors and some components of the fibrinolytic system (plasminogen, α2AP) remained stable. However, plasma concentrations of TAT and D-dimers increased during CPB showing that significant activation of the coagulation and fibrinolytic systems occurred. Mechanisms responsible for the activation of haemostasis are likely complex. However, low plasma concentrations of heparin (<2.0 units/ml in 45% of patients) during CPB were likely a major contributing etiology. ACT values showed a poor correlation (r = 0.38) with heparin concentrations likely due to concurrent haemodilution of haemostatic factors, activation of haemostatic system, hypothermia and activation of platelets. In conclusion, CPB in paediatric patients causes global decreases of components of the coagulation and fibrinolytic systems, primarily by haemodilution and secondarily by consumption.